The Relationship of Children and Their Biological Father (Comparative Study of Positive Law of Indonesia, Thailand and Jordan) - Muhammad Abduh; Amal Fathullah (Syariah: Jurnal Hukum dan Pemikiran, 2022)
Abstract: The civil connection between a child and his biological father is covered in this article. Looking at the legal certainty of a child born as the result of a man and a woman's relationship, whether it be without marriage (adultery) or as the result of a marriage whose validity is not recognized by the state, is in quotation marks (marriage). It will also have an effect on the child's status, which will have an effect on the child's lineage, among the numerous relationship statuses that result in a child. The research's methodology is Law No. 1 of 1974 Concerning Marriage, Thailand Civil and Commercial Code, and Law No. 36 of 2010 Law of Maintenance and Personal Status are the main legal documents used in this comparative research. The method employed is a juridical-comparative, qualitative analysis technique. The author will look at numerous states in Southeast Asia and the Middle East in addition to looking at this issue from the standpoint of Indonesian positive law. Regarding the Asian milestone section, the author will evaluate this issue in light of the State of Thailand's existing and enacted Marriage Law provisions. And for the Middle East, the author will look at the State of Jordan's Marriage Law restrictions. This article utilizes normative juridical research, which takes a comparative approach to law. A comparative technique is employed in this literature review research as an analytical tool to explain the civil relationship provisions that are in place between children and their biological dads in Indonesia, Southeast Asia, and the Middle East.  Abstrak: Hubungan perdata antara seorang anak dengan ayah kandungnya tercakup dalam pasal ini. Menilik kepastian hukum seorang anak yang lahir sebagai hasil hubungan laki-laki dan perempuan, baik tanpa perkawinan (zina) maupun akibat perkawinan yang tidak diakui sahnya oleh negara, dalam tanda kutip (perkawinan). ). Itu juga akan berpengaruh pada status anak, yang akan berpengaruh pada garis keturunan anak, di antara banyak status hubungan yang menghasilkan anak. Metodologi penelitian ini adalah UU No. 1 Tahun 1974 Tentang Perkawinan, Hukum Perdata dan Dagang Thailand, dan UU No. 36 Tahun 2010 Hukum Pemeliharaan dan Status Pribadi adalah dokumen hukum utama yang digunakan dalam penelitian komparatif ini. Metode yang digunakan adalah teknik analisis kualitatif yuridis-komparatif. Penulis akan melihat berbagai negara di Asia Tenggara dan Timur Tengah selain melihat persoalan ini dari sudut pandang hukum positif Indonesia. Mengenai bagian tonggak sejarah Asia, penulis akan mengevaluasi masalah ini dengan mempertimbangkan ketentuan Undang-undang Perkawinan Negara Bagian Thailand yang sudah ada dan berlaku. Dan untuk Timur Tengah, penulis akan melihat batasan Undang-Undang Perkawinan Negara Yordania. Artikel ini menggunakan penelitian yuridis normatif dengan pendekatan hukum komparatif. Teknik komparatif digunakan dalam penelitian tinjauan pustaka ini sebagai alat analisis untuk menjelaskan ketentuan hubungan keperdataan yang berlaku antara anak dan ayah kandungnya di Indonesia, Asia Tenggara, dan Timur Tengah.